Evaluation and antibacterial testing of Mangosteen leaf extract cream (Morinda Citrifolia l) as acne-prone - Kristijono, Ary; Jaroh, Assolychathu; Rosyida, Firdania Firdaus; Prasetya, Bandhi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Acne is a common skin condition caused by the proliferation of bacteria, often leading to inflammation and infection. Morinda citrifolia L. (Noni) has been traditionally used for its medicinal properties, including its antibacterial effects. This study aims to evaluate the antibacterial activity of Noni leaf extract cream and its potential as an acne treatment.. Method: The study involved preparing a cream formulation using ethanol extract of Noni leaves at varying concentrations (1.25%, 2.50%, and 5.00%). The antibacterial activity was tested using the Kirby Bauer disk diffusion method against Streptococcus pyogenes, a common bacterium associated with acne. The cream was also subjected to organoleptic testing, pH testing, viscosity measurements, spreadability tests, and adhesion tests to assess its quality and stability. Results: The cream showed significant antibacterial activity, with a zone of inhibition ranging from 5.79 mm to 9.16 mm, depending on the concentration of Noni leaf extract. The highest antibacterial activity was observed at 5.00% concentration, with a large inhibition zone of 9.16 mm. Additionally, the cream maintained a stable pH and showed good physical properties, including uniform consistency and spreadability. The cream did not exhibit any significant changes in appearance, smell, or texture during the stability testing. Conclusion: The results indicate that Noni leaf extract cream has promising antibacterial effects, particularly at higher concentrations, and could effectively treat acne. The cream demonstrated satisfactory quality and stability, making it a viable candidate for further development in acne treatment formulations.